Pelatihan Sertifikasi Halal Self Declare Produk Unggulan Desa Jombatan Kecamatan Kesamben, Kabupaten Jombang - Wulandari, Sri Yuni; Sulistyowati, Shanti Nugroho (CV. IRA PUBLISHING, 2024)
The need for halal certification continues to increase with increasing consumer awareness of the consumption of halal goods, and the government requires that all products circulating in Indonesia have halal certification to ensure consumer safety and comfort. Self-declaring halal is one step to obtaining halal certification intended for MSMEs. Observation results show that many MSMEs in Jombatan Village do not understand the halal self-declaration certification process and do not know the added value of halal certification; for this reason, they are given training regarding halal certification, the method used in training is through 5 stages to know, to understand, to plan, to act, and to change. Through the training stages, it is known what the actual conditions are in Jombatan Village, then MSME actors are given knowledge about halal certification, and the service team coordinates to plan solutions to problems by providing training programs related to self-declared halal certification; after attending the training MSME actors understand more about the importance product halal certification.